Genome-wide analysis of Hanwoo and Chikso populations using the BovineSNP50 genotyping array - Song, Jun-Seok; Seong, Ha-Seung; Choi, Bong-Hwan; Lee, Chang-Woo; Hwang, Nam-Hyun; Lim, Dajeong; Lee, Joon-Hee; Kim, Jin Soo; Kim, Jeong-Dae; Park, Yeon-Soo; Choi, Jung-Woo; Kim, Jong-Bok (Genes & Genomics, 2018)
Hanwoo and Chikso are classified as Korean native cattle breeds that are currently registered with the Food and Agriculture Organization. However, there is still a lack of genomic studies to compare Hanwoo to Chikso populations. The objective of this study was to perform genome-wide analysis of Hanwoo and Chikso populations, investigating the genetic relationships between these two populations. We genotyped a total of 319 cattle including 214 Hanwoo and 105 Chikso sampled from Gangwon Province Livestock Technology Research Institute, using the Illumina Bovine SNP50K Beadchip. After performing quality control on the initially generated datasets, we assessed linkage disequilibrium patterns for all the possible SNP pairs within 1 Mb apart. Overall, average r 2 values in Hanwoo (0.048) were lower than Chikso (0.074) population. The genetic relationship between the populations was further assured by the principal component analysis, exhibiting clear clusters in each of the Hanwoo and Chikso populations, respectively. Overall heterozygosity for Hanwoo (0.359) was slightly higher than Chikso (0.345) and inbreeding coefficient was also a bit higher in Hanwoo (− 0.015) than Chikso (− 0.035). The average F ST value was 0.036 between Hanwoo and Chikso, indicating little genetic differentiation between those two breeds. Furthermore, we found potential selection signatures including LRP1B and NTRK2 genes that might be implicated with meat and reproductive traits in cattle. In this study, the results showed that both Hanwoo and Chikso populations were not under severe level of inbreeding. Although the principal component analysis exhibited clear clusters in each of the populations, we did not see any clear evidence that those two populations are highly differentiated each other.